Implementasi Metode Langsung dalam Program “Arabic Camp” di Madrasah Ibtidaiyah: Taṭbīq Ṭarīqah al-Mubāsyarah fi Barnamaj “Arabic Camp” bi al-Madrasah al-Ibtidāiyyah - Yasin, Agus; Tazali, Rahmad Maulana; Gandhi, Zain Irsyad (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
This research aims to determine the application of the direct method in the Arabic Camp program at MI PAS Baitul Qur'an Gontor. This research uses descriptive qualitative research, and case study data to implement direct methods in the "Arabic Camp" program. Research data collection techniques use observation, interviews, and documentation of data sources in research. The data taken comes from teacher interviews, exam documentation scores, and other related documentation using the Miles and Huberman model data analysis techniques. The research results show that applying direct methods in the Arabic Camp program can improve students' language skills. Because, during this program the participants are accustomed to listening and using Arabic both during learning and in other activities. Apart from that, some problems arise from factors such as students, teaching staff, or time/atmosphere in the Arabic camp program. From this it can be concluded that the direct method applied at Madrasah Ibtidaiyah is under child development theory which is aligned with children's language learning abilities, which is said to be the same as a mother teaching her child their first language.